2013
DOI: 10.1016/j.jamcollsurg.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Operations Performed by Attending Surgeons after Overnight Trauma Shifts

Abstract: BACKGROUND To date, work-hour restrictions have not been imposed on attending surgeons in the United States. The purpose of this study was to investigate the impact of working an overnight trauma shift on outcomes of general surgery operations performed the next day by the post-call attending physician. STUDY DESIGN Consecutive patients over a 3.5-year period undergoing elective general surgical procedures were reviewed. Procedures were limited to hernia repairs (inguinal and ventral), cholecystectomies, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Finally, no difference in readmission rates was observed among patients operated on by general surgeons after providing a trauma call (20). When considered alongside these data, our findings are was defined as beginning between midnight and 6:59 AM, whereas next-day PCI procedures included those which began between 7 AM and midnight on the same date.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, no difference in readmission rates was observed among patients operated on by general surgeons after providing a trauma call (20). When considered alongside these data, our findings are was defined as beginning between midnight and 6:59 AM, whereas next-day PCI procedures included those which began between 7 AM and midnight on the same date.…”
Section: Discussionmentioning
confidence: 89%
“…[11,12] Sharpe et al studied the effects of attending surgeons working the day after a night on call and found no difference in the complication or readmission rates. [13] One study that tested the effects of sleep deprivation on physicians and non-physicians reported less variation in performance in the physician group, possibly because those test subjects were “used to” performing with little sleep. [14] Further, studies have shown adaptation to sleep deprivation after three nights, which would explain why experienced surgeons who are presumably adapted to sleeplessness did not show a difference in performance with acute sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The results of studies exploring clinical outcomes have been mixed, but a systematic review showed that a prolonged duration of sleeplessness, which would result from the provision of overnight medical care, significantly reduces clinical performance. [8][9][10][11][12] The published studies on this topic have had small samples and few events, resulting in limited statistical power. This literature has contributed to the current duty-hour restrictions mandated in all North American residency training programs.…”
mentioning
confidence: 99%